2007
DOI: 10.1007/s00221-007-1093-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of transcranial direct current stimulation on the excitability of the leg motor cortex

Abstract: Transcranial direct current stimulation (tDCS) of the human motor cortex at an intensity of 1 mA has been shown to be efficacious in increasing (via anodal tDCS) or decreasing (via cathodal tDCS) the excitability of corticospinal projections to muscles of the hand. In this study, we examined whether tDCS at currents of 2 mA could effect similar changes in the excitability of deeper cortical structures that innervate muscles of the lower leg. Similar to the hand area, 10 min of stimulation with the anode over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
174
2
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 211 publications
(187 citation statements)
references
References 28 publications
8
174
2
3
Order By: Relevance
“…These areas are less easily approached with NIBS techniques, especially when dealing with distal muscles. However, studies on healthy individuals have demonstrated that rTMS, tDCS, and PAS protocols are able to modulate the excitability of the leg motor cortex, 82,99,117 and a behavioral effect of anodal tDCS on lower-limb motor performance, as transient enhancement of maximal leg force, has been observed. 118 Because the pathophysiological reorganization of leg motor areas after stroke is still unclear, based on the model of interhemispheric competition after stroke established for the upper extremity, NIBS techniques have been mainly applied for inhibiting the unlesioned hemisphere or facilitating the lesioned hemisphere.…”
Section: Nibs and Lower-limb Motor Recovery After Strokementioning
confidence: 99%
“…These areas are less easily approached with NIBS techniques, especially when dealing with distal muscles. However, studies on healthy individuals have demonstrated that rTMS, tDCS, and PAS protocols are able to modulate the excitability of the leg motor cortex, 82,99,117 and a behavioral effect of anodal tDCS on lower-limb motor performance, as transient enhancement of maximal leg force, has been observed. 118 Because the pathophysiological reorganization of leg motor areas after stroke is still unclear, based on the model of interhemispheric competition after stroke established for the upper extremity, NIBS techniques have been mainly applied for inhibiting the unlesioned hemisphere or facilitating the lesioned hemisphere.…”
Section: Nibs and Lower-limb Motor Recovery After Strokementioning
confidence: 99%
“…Among research on agility in accordance with tDCS application, Boggio et al 31) reported that performance time decreased in their study of hand response speed, and Kim Joong-sun et al 32) also reported reduced response times. Jeffery et al 17) observed improved performance and increased response time of the lower extremities in normal subjects. According to the present study results, tDCS application may effectively enhance normal people's agility, and the resulting activation of the motor cortex has a sustained influence on treadmill gait, as asserted by Antal et al 7) .…”
Section: Discussionmentioning
confidence: 95%
“…Noninvasive tDCS has drawn attention as a potential area of research on neurological reversibility through its application to the premotor area 29,30) . Although research on tDCS application to the upper extremity areas has been active, research on its application to the lower extremity areas has concerned only response time and single muscle activity 17) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations